The interaction between consumers during the online customer journey - Nieminen, Päivi (2017)
The examination of the customer experience throughout customer journey is important to the business and academia. Creating a strong and positive experience within the customer journey will lead to better outcome by improving performance in customer travel at multiple touch points and through enhanced customer loyalty and word of mouth. There are a number of studies about interaction and online customer journey, but only a few research have explored social interactions between consumers during the online customer experience. The aim of this study is to explain how interaction between customers emerges during the online customer journey, which describes the overall customer experience from the consumer’s point of view. This includes the motives to share and search content that is generated by consumers during the online customer journey, but the study is also interested in how these motives varies at different stages of the online customer journey and in which channels the interaction takes place during the online customer journey. This study is causal in nature. A quantitative research approach was implemented to gather information with a structured online survey questionnaire. The target audience of this study was a Finnish online consumers. Data was collected with an online survey and it yield-ed 237 responses. Data was analyzed with SPSS and the relationships between the constructs were tested by Amos Graphics 24. Result of this study suggests that the interaction between customers emerges the during online customer journey as sharing and searching word of mouth (WOM) content. The sharing WOM contents is much less common than searching WOM contents during the online customer journey, which is align with research of Bernstein et al. (2013). According to this study, customers are searching WOM contents at every stage of the online customer journey, which is consistent with the research of King et al. (2014). The motives of empirical models to share or search WOM content during online customer journey do not explain the sharing or searching behavior. The motives to search WOM content during online customer journey affect indirectly through opinion seeking behavior and curating skills. Results of this study also suggest that the customers share their WOM content partly in another channels than they are searching WOM content during the online customer journey.